Nationally executed programme/project management - Mercado, Cesar Matamorosa 1938- (Development Consultants for Asia Africa Pacific, 2004)
Purpose: "The purpose of this handbook is to help national and international project managers and staff and other interested parties understand and appreciate the new modality in executing UN-assisted programmes/projects." The handbook focuses primarily on the new Nationally Executed Programme/Project concepts, principles, paradigms, structures and activities."